Development and Validation of the Satisfaction Survey for Inflatable Penile Implant (SSIPI). Issue 9 (6th August 2021) - Salter, Carolyn A.; Bach, Philip Vu; Jenkins, Lawrence; Bennett, Nelson; Yafi, Faysal A.; el Khatib, Farouk; Schofield, Elizabeth; Benfante, Nicole; Althof, Stanley E.; Nelson, Christian J.; Mulhall, John P.
ABSTRACT: Background: No validated English language patient-reported outcome (PRO) currently exists that assesses satisfaction with inflatable penile prosthesis (IPP). Satisfaction data have been largely based primarily on surgeon assessment of patients or using questionnaires that have not been designed for this purpose. Aim: To develop an English-language validated PRO that assesses patient satisfaction after IPP surgery. Methods: Initially, a literature review and discussions with experts defined domains important to IPP satisfaction (pain, appearance, function, overall satisfaction). The initial 35-item Satisfaction Survey for Inflatable Penile Implant (SSIPI) was developed. Cognitive interviews were then performed with IPP patients (n = 12) to gain feedback on the SSIPI domains and items. These data were used to modify SSIPI with the addition of 2 questions for a final item number of 37. Patients from 4 centers, who were between 6 months and 5 years after IPP, were administered the questionnaire through RedCap. Reliability statistics and content analysis were used to winnow questions to yield the final 16-item version of the SSIPI. Internal consistency was assessed via Cronbach's alpha and item-total correlation. Test-retest reliability was assessed via intraclass correlation coefficients using baseline and 2-week data. For convergent validity, the Erectile Dysfunction Inventory of Treatment Satisfaction and the Self-Esteem and Relationship (SEAR) questionnaire were used. For discriminant validity, the International Prostate Symptom Score (IPSS) was used. Confirmatory factor analysis was used to assess the factor structure of the SSIPI. Outcomes: Internal consistency, test-retest reliability, convergent and discriminant validity, and confirmatory factor analysis were assessed. RESULTS: 118 men were surveyed. Mean age was 66.8 ± 9.5 years. The 16-item SSIPI showed high internal consistency with an overall Cronbach's Alpha of 0.97 (domains 0.85–0.89). Item-total correlations for individual items to subscales ranged from 0.60 to 0.91. The overall test-retest reliability was 0.94 (domains 0.87–0.93). Erectile Dysfunction Inventory of Treatment Satisfaction and Self-Esteem and Relationship had correlations of 0.84 overall (domains 0.57–0.79) and 0.47 overall (domains 0.34–0.44), respectively. International Prostate Symptom Score (discriminant validity) had correlations of -0.29 overall (domains -0.17 to -0.31). Clinical Implications: SSIPI is the first English-language validated IPP satisfaction PRO. This will enable clinicians to collect satisfaction data in a standardized way. Strengths and Limitations: As strengths we have used a rigorous psychometric process and have no industry sponsorship. Limitations include small numbers of specific subpopulations. CONCLUSION: The SSIPI has demonstrated robust psychometric properties.